Chloroplast protein import in stress and disease - Sowden, RG (2019)
There is a growing body of evidence that demonstrates that plants and pathogens compete over the chloroplast to activate or disable immunogenic signalling. A critical event in the initiation of immunity is the generation of a reactive oxygen species (ROS) burst in the chloroplast with energy diverted from photosynthesis. Here, it is shown that model bacterial pathogen Pseudomonas syringae suppresses chloroplast protein import to subvert the chloroplast ROS burst and facilitate infection.